Pengaruh Kejenuhan Kerja Dan Keseimbangan Kehidupan Kerja Terhadap Kepuasan Karyawan Pada Pt. Fvs Arthadharma Indonesia Kota Bandung - Siregar, Jimmy Rian Rinaldi; Rizaldi, Arjuna (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2024)
The purpose of this study was to determine work saturation and work life of employees at PT. FVS Arthadharma Indonesia Bandung City. and to determine the effect of work saturation and work life at PT. FVS Arthadharma Indonesia Bandung City on employee job satisfaction, either partially or concurrently. In this study, a quantitative technique is used with descriptive and verifiable methodologies. There were fifty responders in the research sample. Data collection techniques using questionnaires and interviews while data analysis techniques with multiple regression analysis. The results showed that work saturation and work life at PT. FVS Arthadharma Indonesia Bandung City.classified as good, employee job satisfaction at PT. FVS Arthadharma Indonesia Bandung City.generally categorized as good. The results of hypothesis testing show that Role Conflict and Role Ambiguity have a positive and significant effect on Employee Job Satisfaction both partially and Sim.